Tourism in Pakistan, Challenges and Opportunities (Journal of Social Sciences Review, 2022)
The tourism sector in Pakistan has tremendous potential and is linked to some of the tallest mountains, lakes, and natural sceneries in the country, and it is a well-liked attraction for visitors from both inside and outside the nation. In addition to generating cash, tourism also helps to promote a particular country's culture; hence, it should be seen as an essential component of Pakistan's growth plan. The diversity of its cultures, civilizations, and customs has tragically prevented Pakistan from realising its full tourism potential. To become the most well-liked tourist destination in the world, Pakistan would have to overcome several difficulties in the tourism industry. This essay examines the difficulties the tourism industry faces using research from Pakistan. According to the report, Pakistan's security and counterterrorism issues have negatively impacted travel and tourism. But it is now generally acknowledged that Pakistan is transforming into a welcoming and secure environment for everyone. This essay also includes explanations of suggestions for the tourist industry.
Keywords: Tourism; Pakistan; opportunities; Society